2018
DOI: 10.1093/brain/awx352
|View full text |Cite|
|
Sign up to set email alerts
|

Synaptic markers of cognitive decline in neurodegenerative diseases: a proteomic approach

Abstract: See Attems and Jellinger (doi:10.1093/brain/awx360) for a scientific commentary on this article.Cognitive changes occurring throughout the pathogenesis of neurodegenerative diseases are directly linked to synaptic loss. We used in-depth proteomics to compare 32 post-mortem human brains in the prefrontal cortex of prospectively followed patients with Alzheimer's disease, Parkinson's disease with dementia, dementia with Lewy bodies and older adults without dementia. In total, we identified 10 325 proteins, 851 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
137
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(150 citation statements)
references
References 66 publications
6
137
0
2
Order By: Relevance
“…Consistently, in both Banner and BLSA, we found that lower abundance of SNAP25 was associated with faster cognitive decline. Furthermore, Bereczki and colleagues performed a comprehensive study of 851 synaptic proteins in neurodegenerative diseases and cognitive decline 51 . They found that reduced levels of synaptic proteins SNAP47, SYBU, LRFN2, SV2C, and GRIA3 were associated with cognitive impairment and faster cognitive decline 51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, in both Banner and BLSA, we found that lower abundance of SNAP25 was associated with faster cognitive decline. Furthermore, Bereczki and colleagues performed a comprehensive study of 851 synaptic proteins in neurodegenerative diseases and cognitive decline 51 . They found that reduced levels of synaptic proteins SNAP47, SYBU, LRFN2, SV2C, and GRIA3 were associated with cognitive impairment and faster cognitive decline 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Bereczki and colleagues performed a comprehensive study of 851 synaptic proteins in neurodegenerative diseases and cognitive decline 51 . They found that reduced levels of synaptic proteins SNAP47, SYBU, LRFN2, SV2C, and GRIA3 were associated with cognitive impairment and faster cognitive decline 51 . Among these proteins, only GRIA3 was detected in our datasets and had lower abundance in faster cognitive decline in both Banner and BLSA, consistent with Bereczki and colleagues' finding.…”
Section: Discussionmentioning
confidence: 99%
“…CSF Ng levels have been extensively investigated in Alzheimer's disease (AD), where they are increased compared to controls, increased in amyloid‐beta (Aβ) + mild cognitive impairment (MCI), and linked to cognitive decline and progression from MCI to AD dementia . A recent postmortem, human brain proteome study on patiens with and without dementia found that synaptic proteins, but not any individual protein, could differentiate PD with dementia (PDD) and dementia with Lewy bodies (DLB) from controls and AD and that cognitive impairment and decline in life correlated with loss of synaptic proteins …”
mentioning
confidence: 99%
“…4,6-8,10,11 A recent postmortem, human brain proteome study on patiens with and without dementia found that synaptic proteins, but not any individual protein, could differentiate PD with dementia (PDD) and dementia with Lewy bodies (DLB) from controls and AD and that cognitive impairment and decline in life correlated with loss of synaptic proteins. 12 Few studies have examined CSF Ng in PD, finding unchanged or decreased levels of Ng compared to controls. 5,9,13 Even scarcer are studies on Ng and cognitive decline or motor dysfunction, and results are conflicting.…”
mentioning
confidence: 99%
“…Similarly, synaptic loss is a common theme across all neurodegenerative disease, but genetic enrichment in specific synaptic modules is not observed universally. The downregulated C1 module was dysregulated exclusively in neurodegenerative dementia cases (AD, FTD-TDP), and not other neurodegenerative conditions suggesting that this module may contribute to shared pathogenic pathways related to cerebral cortical dysfunction (Bereczki et al, 2018;Bigio et al, 2001;Clare et al, 2010;Hassan et al, 2011). Interestingly, this synaptic C1 module was enriched for common genetic variants in PSP, indicating that these synaptic variants may be causal drivers of PSP, but not AD.…”
Section: Discussionmentioning
confidence: 96%